2018
DOI: 10.1021/acs.analchem.8b03594
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Multiple-Monomeric-Peak Profile of Broadly Neutralizing HIV-1 Antibody 10E8 with a Unique Size-Exclusion-Chromatography Method

Abstract: 10E8 is a potent broadly neutralizing antibody (bNAb) that targets the membrane-proximal external region (MPER) of the HIV virus. During early analytical development of this bNAb directed towards clinical evaluation, 10E8 exhibited a multiple-monomeric-peak profile caused by secondary interactions in traditional size-exclusion chromatography (SEC), thereby rendering SEC unfit for the purpose of assessing aggregation, a target critical quality attribute. To overcome this challenge, an innovative and robust SEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…To investigate the apparent heterogeneity of 10E8 we performed SEC under a series of conditions. As reported previously 7 , 8 , 22 , 10E8 showed elution profiles with multiple peaks. When performing SEC with a monolayer coated silica matrix (Sepax, SRT), three baseline resolved peaks (here denoted as “SEC peaks 1–3”) were observed that eluted much later than expected based on standard protein molecular weight markers (Fig.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…To investigate the apparent heterogeneity of 10E8 we performed SEC under a series of conditions. As reported previously 7 , 8 , 22 , 10E8 showed elution profiles with multiple peaks. When performing SEC with a monolayer coated silica matrix (Sepax, SRT), three baseline resolved peaks (here denoted as “SEC peaks 1–3”) were observed that eluted much later than expected based on standard protein molecular weight markers (Fig.…”
Section: Resultssupporting
confidence: 85%
“…1 B). Previous studies have shown that the SEC resolved 10E8 peaks corresponded to single IgGs that are in a slow dynamic equilibrium 7 , 8 , 22 . To confirm that our 10E8 was similarly behaved we performed SEC with multi-angle light scattering (MALS) and observed three peaks, each of which had a molecular mass near 150 kDa consistent with an intact IgG, as reported previously (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations